Between the continuity imperative and the risk of exclusion: Juvenile views about Accompaniment to their School Trajectories during pandemic (Praxis Educativa, 2022)
This paper states results from a research project focused on the analysis of school trajectories and access to Secondary School by youngsters from low income sectors of the city of Cordoba. Understanding that analysis and assessment of educational accessibility guidelines during pandemic must take especially into account the views, experiences and meanings of its target population, we analyze a set of interviews conducted at a secondary school during May 2021. Our findings indicate the relevance of school agents and their key role in sustaining their schooling. However, we also address some minor statements that take a critical stance towards the quality of learning processes and strategies implemented, providing significant elements to reflect about educational continuity during pandemic within a fragmented school system.
Keywords: secondary school; access to education; urban youngsters; disadvantage groups; panemics